If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6x + 2 + 7x = 14 + -24 Reorder the terms: 2 + -6x + 7x = 14 + -24 Combine like terms: -6x + 7x = 1x 2 + 1x = 14 + -24 Combine like terms: 14 + -24 = -10 2 + 1x = -10 Solving 2 + 1x = -10 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 1x = -10 + -2 Combine like terms: 2 + -2 = 0 0 + 1x = -10 + -2 1x = -10 + -2 Combine like terms: -10 + -2 = -12 1x = -12 Divide each side by '1'. x = -12 Simplifying x = -12
| -6(3xx-9)=-234 | | 6-2x-1=4+8-6x | | 4-4x=9-9x | | 2(x+4)=3(x-3) | | 1.7t-4.5=7.75 | | 9+3x=2-4x | | 10x+5y=35 | | 6z=3z-8+2z | | (50*45)/60+5= | | 3(4-x)=5+4x | | k/15=18 | | 5.1+1.9x=2.9x | | 3(3x+1)=8(x+1) | | 17-5x=3x+1 | | 2+3x=58 | | 2x-2+x=4+5 | | 18-4h=-10-4h | | 6x^2y^2-52xy^2-210y^2=0 | | 12-6x=9-7x | | 2x^2=4xs | | 2(w-3)+7=1-2w | | 4-x=x | | x^5+x^2+x=0 | | 8x+4=5(x+2) | | 9.40dm=hm | | X-2x=3x-20 | | 6(7+2x)-8x-(y+4)=12 | | 7x+8-x+7=3x+24 | | (x-3)2=15 | | -24=t-29 | | 40-13x=1 | | x^2-4x+6y+10=0 |